Enabling Activities Facilitating EFL Students to Participate in Learning English - Judith Ratu (LPPM UKI Toraja, 2017)
Teacher needs to think how to engage students to have participation in learning English. This article consists of brief about activities facilitating EFL students to participate in learning English. It is to identify and explain the activities: group work, song, chant, poem, finger plays, story telling on tablet PCs, using drama, project work, games and other activities outside of the classroom. These activities can be used by the teacher to help the students to engaged and encourage the students to study more about English.